Mastering Stocks and Bonds - Emons, Ben. author. aut Link
IX, 205 p.
Keywords: Despite popular belief, bond and stock investors are not opposites. Stock investors can apply bond strategies to safeguard returns. And bond investors can do better using a stock selection strategy designed to improve the portfolio's income distribution. This book will teach you to look at stocks through the lens of a bond buyer, and vice versa.